Evaluation of Potential Herb-Drug Interactions Between Shengmai Injection and Losartan Potassium in Rat and In Vitro - Niu, Zhenchao; Qiang, Tingting; Lin, Wenyong; Li, Yiping; Wang, Keyan; Wang, Dan; Wang, Xiaolong (Frontiers in Pharmacology, 2022)
Aim: The present study aimed to explore the mechanisms of the increased antihypertensive effect of losartan potassium following its combination with Shengmai injection (SMI). Methods: Different concentrations of SMI were used to explore the influence of SMI on the antihypertensive efficacy of losartan potassium (LOS) in the hypertension rat model established by L-NAME for 4 weeks. Subsequently, the serum concentration levels of LOS and EXP3174 were determined by LC-MS and pharmacokinetic analysis. Human liver microsomes, human MDR1, and BCRP vesicles, HEK293-OATP1B1, and HEK293-MOCK cells were used to verify the effects of SMI on CYP450 enzymes and drug transporters in vitro. Results: Low, medium, and high concentrations of SMI increased the antihypertensive efficacy of LOS at varying degrees. The high dose SMI increased the t1/2, Cmax, AUC0-t, AUC0-∞, and MRT values of LOS and decreased its Vd and CL values. The Auc0-t, AUC0-∞, and MRT of LOS were increased, whereas the CL was decreased by the medium concentration of SMI. In addition, the high, medium, and low doses of SMI increased the Frel of LOS. SMI exhibited no significant effects on the pharmacokinetics of EXP3174. In vitro, SMI exhibited different suppressive effects on the enzyme activity levels of CYP1A2 (6.12%), CYP2B6 (2.72%), CYP2C9 (14.31%), CYP2C19 (12.96%), CYP2D6(12.26%), CYP3A4 (3.72%), CYP2C8 (10.00-30.00%), MDR (0.75%), OATP1B1(2.03%), and BCRP (0.15%). Conclusion: SMI can enhance the antihypertensive efficacy of LOS in the L-NAME-established hypertension rat model by increasing the exposure of LOS and not by affecting EXP3174. SMI affected the pharmacokinetic properties of LOS by increasing the absorption of LOS and decreasing distribution, metabolism, and excretion of LOS, which was partly due to the inhibitory effects on the enzyme activities of CYP3A4, CYP2C9 (drug-metabolizing enzymes), P-gp, BCRP, and OATP1B1 (drug transporters) caused by SMI.